2011
DOI: 10.1007/s10157-011-0550-x
|View full text |Cite
|
Sign up to set email alerts
|

Extragastrointestinal stromal tumor in a kidney transplant recipient

Abstract: The occurrence of de novo malignant neoplasms has been shown in post-transplant recipients receiving immunosuppressive treatment. We present a case of a rare extragastrointestinal stromal tumor (EGIST) located in the pelvic cavity of a kidney transplant patient. A 57-year-old female patient was admitted to our department because of non-specific lower abdominal pain 6 months after renal transplantation. An abdominal computed tomography scan showed a 4.5 cm diameter pelvic tumor mass. The tumor was resected en b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 18 publications
0
5
0
1
Order By: Relevance
“…No previous reports exist about this SNP in RCC. Its presence has been reported in rare cancers such as extra-intestinal stromal tumors and cervical adeno-squamous carcinoma, nevertheless its prognostic or predictive role remains largely unexplored [ 32 , 33 ]. In our series we could not confirm a variation in response to different PDGFR-inhibitors such as sunitinib or sorafenib based on the presence of this SNP.…”
Section: Discussionmentioning
confidence: 99%
“…No previous reports exist about this SNP in RCC. Its presence has been reported in rare cancers such as extra-intestinal stromal tumors and cervical adeno-squamous carcinoma, nevertheless its prognostic or predictive role remains largely unexplored [ 32 , 33 ]. In our series we could not confirm a variation in response to different PDGFR-inhibitors such as sunitinib or sorafenib based on the presence of this SNP.…”
Section: Discussionmentioning
confidence: 99%
“…The remaining three cases (10.34%, 3/29) were represented by a D842V point mutation on exon 18, associated with a lack of KIT expression, which was observed in 37.50% (3/8) of the CD117-negative cases. Tu et al (22) reported the case of a renal transplant recipient with a GIST, in which a Val824 internal GTC>GTT base point mutation was identified in PDGFRA with no KIT mutations present. This was the second report of this type of mutation, which coexisted with the L576P point mutation on exon 11.…”
Section: Discussionmentioning
confidence: 99%
“…Tu et al 9 presented a case of a rare extra-gastrointestinal stromal tumour (EGIST) located in the pelvic cavity of a patient with kidney transplantation. A 57-year-old woman was admitted due to non-specific abdominal pain 6 months after transplantation.…”
Section: Discussionmentioning
confidence: 99%